2001
DOI: 10.1046/j.1444-2906.2001.00335.x
|View full text |Cite
|
Sign up to set email alerts
|

Ultrastructure of the oocytes of the Japanese eel Anguilla japonica during artificially induced sexual maturation

Abstract: Morphological changes in the oocytes of the Japanese eel, Anguilla japonica, induced to undergo ovarian development by repeated injections of salmon pituitary homogenate, were examined using electron microscopy. Oil droplets were closely associated with organelles, especially mitochondria, and increased in number as oocyte growth proceeded. They fused at the migratory nucleus stage. During vitellogenesis, two types of cortical alveoli were distinguished, one having filamentous contents, the other having lattic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…Authors reported a proliferation of mitochondria in gonad ooplasm after hormonal treatment with CPE (Burzawa-Gérard et al 1994). Such a report was also established from oocytes of female Anguilla japonica artificially matured with salmon pituitary extracts (Kayaba et al 2001). Whereas few and undeveloped mitochondria were observed in gonad of immature/ untreated animals (oocytes at the oil droplet stage), a large number of developed mitochondria were r = 0.72 P = 0.00065 Fig.…”
Section: Discussionmentioning
confidence: 90%
“…Authors reported a proliferation of mitochondria in gonad ooplasm after hormonal treatment with CPE (Burzawa-Gérard et al 1994). Such a report was also established from oocytes of female Anguilla japonica artificially matured with salmon pituitary extracts (Kayaba et al 2001). Whereas few and undeveloped mitochondria were observed in gonad of immature/ untreated animals (oocytes at the oil droplet stage), a large number of developed mitochondria were r = 0.72 P = 0.00065 Fig.…”
Section: Discussionmentioning
confidence: 90%
“…Vitellogenesis is an important phase of oocyte development of oviparous animals, in which oocytes accumulate nutrients required for embryonic and larval development and its duration is extremely variable between species (Kayaba et al., ; Jalabert, ). In P. vittata , yolk globules proved to be intact and remained until the end of oocyte maturation.…”
Section: Discussionmentioning
confidence: 99%
“…These results suggest that lipid delivered to the liver was further transported to the ovary, and that the observed decrease after the mid‐vitellogenic stage reflects the process by which ovarian growth caused the accumulation of other materials, mainly vitellogenin. Several reports suggested that after SPH injection, oil droplets in oocytes were immediately increased in both number and size, while yolk globules began to increase later 23,24 . Moreover, it was reported that the serum vitellogenin levels and vitellogenin transcripts were gradually increased after SPH injection and peaked at the migratory nucleus stage 22,25 .…”
Section: Discussionmentioning
confidence: 99%
“…Several reports suggested that after SPH injection, oil droplets in oocytes were immediately increased in both number and size, while yolk globules began to increase later. 23,24 Moreover, it was reported that the serum vitellogenin levels and vitellogenin transcripts were gradually increased after SPH injection and peaked at the migratory nucleus stage. 22,25 These observations suggest that most of the lipids Fig.…”
Section: Discussionmentioning
confidence: 99%